Combining ability and gene action studies for yield and fibre traits in Gossypium arboreum using Griffings numerical and Haymans graphical approach - Bhimireddy SUKRUTHA; Sivakami RAJESWARI; N. PREMALATHA; Narayana Manikanda BOOPATHI; K. THIRUKUMARAN; A. MANIVANNAN (Journal of Cotton Research, 2023)
Abstract Background For the purpose of utilising hybrid vigour to produce possible hybrids with a suitable level of stability, the knowledge of gene activity and combining ability is a crucial prerequisite before choosing desirable parents. The present study was carried out with six parents crossed in full diallel fashion and generated 30 F1 hybrids. These hybrids were evaluated in two replications in Randomized Block Design at Department of Cotton, TNAU for combining ability and gene action. Diallel analysis was carried out according to Griffing’s method-I (parents + F1 + reciprocals) and model-I and Hayman’s graphical approach by using INDOSTAT software. Results Analysis of variance for combining ability indicated that mean square values of GCA, SCA and reciprocals were highly significant for all the traits except for the uniformity index. RG763 and K12 showed highly positively significant GCA effects for most of the yield traits while PA838 and K12 for fibre quality traits, so they were found as best general combiners. PAIG379 × K12 and PDB29 × K12 for yield traits, and PDB29 × PA838, RG763 × PA838, and CNA1007 × RG763 cross combinations for fibre quality traits could be recommended for future breeding programms. Conclusion The results of both Griffing’s and Hayman’s approaches showed that non-additive gene action predominates as SCA variance was bigger than GCA variance, so heterosis breeding is thought to be a more fruitful option for enhancing GCA of many traits.